FAKTOR â FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS STUDI KASUS KPP SEMARANG TENGAH DUA - Wulan Sari, 08.05.52.0133; Kartika, Andi (Students Journal of Accounting and Banking, 2012)
Tax is the stateâs biggest income, however number of taxpayers, although the number of taxpayers are increasing rapidly in Indonesia, there are obstacles to increase the tax ratio, which are the complianceof the must pay tax.This study investigated the level of compliance of individual income taxpayers in KPP Pratama Semarang Tengah Dua by using several independent variables have been used in previous research such as knowledge about tax, perception to tax employees, criteria good tax payers, the awareness in compliance must pay tax, sanction of tax and service taxpayers.Keywords: Compliance of Must Pay tax, knowledge of tax, criteria good taxpayers, perception to tax employees Sanction of Taxation, The Awareness in Compliance Must Pay Tax, Service Taxpayers, and Individual Income Tax.